Effectiveness of From Timid To Tiger Program on Clinical Symptoms of Children with Separation Anxiety Disorder and Family Accomadation of Their Parents - Mohsen Jalali; Elnaz Pourahmadi Esfastani (روانشناسی بالینی و شخصیت)
Introductin:The aim of this study was to evaluate the effectiveness of the  to Tiger program on the clinical symptoms of children with Separation Anxiety Disorder (SAD) and the family accommodation of their parents.Method: This study employed a semi-experimental research design that included pretests, post-tests, and follow-up assessments with a control group. The statistical population of the research consisted of children with anxiety in Gorgan and their mothers. Thirty-six children were selected using purposive sampling as the research sample and were randomly allocated into experimental and control groups. The Timid to Tiger Program was conducted in 10 sessions for parents in the experimental group. To evaluate the effect of the intervention, the Spence Anxiety Scale and the Family Accommodation Scale were administered to the mothers of all participating children at the beginning, the end of treatment, and during the follow-up stage. Finally, analysis of covariance and the improvement percentage formula were utilized to analyze the data.Results: The results indicated a significant reduction in anxiety among children and improved family accommodation among parents in the experimental group compared to the control group, as observed in both the post-test and follow-up (P < 0.05). The results of clinical significance indicated that the anxiety levels of children and the family accommodation of parents in the experimental group significantly improved compared to the control group in both the post-test and follow-up assessments.Discussion and Conclusion: The FormTimid to Tiger Program is effective in reducing anxiety in children with Separation Anxiety Disorder and in enhancing parental accommodation. The results of this research, along with similar studies, can be applied in the fields of diagnosis and therapy for anxiety disorders in children.